The critical discourse of literature - Ballón Aguirre, Enrique (1985)
Paper presented at the IV International Symposium on Poetics and Semiology convened by the Poetics Seminar of the Institute of Philological Research of the Autonomous University of Mexico (UNAM), held during the month of November 1981.